The Influence of Auditor Quality and Follow-Up Audit Resolution on Organizational Effectiveness: A Case Study at the Regional Inspectorate of Way Kanan Regency - Senen Mustakim; David Ariswandy; Epi Parela (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Success in internal audit is determined by the quality of auditors and the completion of audit results in achieving the stated organizational effectiveness. Organizational effectiveness is a management system to achieve several goals and objectives. The better the quality of the auditors in presenting the audit results report, the easier it will be for the auditee to resolve follow-up audit results, this will support the achievement of organizational goals. This shows that auditors can act as consultants who carry out audits, auditors also participate in conveying problems related to the company / organization. The type of research used in this research is quantitative descriptive research model. This study used 30 research respondents. There are three variables in this study, namely: 2 (two) independent variables (X₁ and X₂) and 1 (one) dependent variable where the quality of the auditor (X₁) and the completion of the follow-up of audit results (X₂) are independent variables and organizational effectiveness as the dependent variable. . From the results of data processing, the following hypothesis answers have been found: there is an effect of auditor quality (X₁) on organizational effectiveness (Y), with a level of influence (R-square) of 52.8%, which means that the quality of auditors has an effect of 52.8%. Against organizational effectiveness. There is an influence between the completion of the follow-up of the audit results (X₂) on organizational effectiveness (Y), with a level of influence of 52.7%, which means that the completion of the follow-up of the audit results has an effect of 52.7% on organizational effectiveness (Y). Regarding the effect of auditor quality (X₁), completion of the follow-up of audit results (X₂) with organizational effectiveness (Y), with a level of influence (R-square) of 60.4% which means that the quality of auditors and completion of the follow-up of audit results have an effect of 60, 4% on organizational effectiveness. Keywords: Auditor Quality, Follow Up, Organizational Effectiveness